Development of the experimental stand with centrally located specimen for the investigation of heat and moisture phenomena in porous building materiale = Rozwój stanowiska doświadczalnego z centralnie umieszczoną próbką do badań procesu grzania i suszenia porowatych materiałów budowlanych - Cieślikiewicz, Łukasz; Wasiak, Michał; Kubiś, Michał; Łapka, Piotr; Bugaj, Marcin; Pietrak, Karol; Wiśniewski, Tomasz S.; Furmański, Piotr; Seredyński, Mirosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents development of an experimental stand with centrally located specimen for the investigation of heating and drying processes in porous building materials. Additionally, the paper contains preliminary results of measurements which test and verify the assumed operation conditions of the stand.
Keywords: drying of porous materials; drying measurements; building materials; experimental stand; suszenie materiałów; pomiary procesu suszenia; materiały budowlane; stanowisko doświadczalne